(untitled) (Journal of Engineering, 2014)
Anaerobic digestion is a technology widely used for treatment of organic waste for biogas production as a source for clean energy. In this study, poultry house wastes (PHW) material was examined as a source for biogas production. The effects of inoculum addition, pretreatment of the substrate, and temperature on the biogas production were taken into full consideration. Results revealed that the effect of inoculum addition was more significant than the alkaline pretreatment of raw waste materials. The biogas recovery from inoculated waste materials exceeds its production from wastes without inoculation by approximately 70% at mesophilic conditions. Whereby, the increase of biogas recovery from pretreated wastes was by 20% higher than its production from untreated wastes at mesophilic conditions. The thermophilic conditions improved the biogas yield by approximately 73%. The kinetic of bio-digestion process was well described by modified Gompertz model and the experimental and predicted values of biogas production were fitted well with correlation coefficient values > 0.96 suggesting favorable conditions of the process.